2008
DOI: 10.1303/aez.2008.219
|View full text |Cite
|
Sign up to set email alerts
|

Sex attractant pheromone of the sorghum plant bug Stenotus rubrovittatus (Matsumura) (Heteroptera: Miridae)

Abstract: The sorghum plant bug Stenotus rubrovittatus (Matsumura) (Heteroptera: Miridae) is a major seed pest of rice in Japan. Male S. rubrovittatus were previously shown to be attracted to traps baited with unmated females. The solvent extract of unmated females was analyzed by GC-MS using HP-INNOWax and HP-5ms columns, and retention index data and mass spectra of peaks detected in the female extract were compared with those of authentic samples. Three compounds, hexyl butyrate (ϭbutanoate), (E)-hex-2-en-1-yl butyrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 24 publications
2
48
0
Order By: Relevance
“…In Japan, the aggregation pheromones of Plautia crossota stali Scott (Heteroptera: Pentatomidae) (Sugie et al, 1996), Riptortus pedestris (Fabricius) (Heteroptera: Alydidae) (ϭR. clavatus) (Leal et al, 1995) and Eysarcoris lewisi (Distant) (Heteroptera: Pentatomidae) (Takita et al, 2008), and the sex pheromones of Piezodorus hybneri (Gmelin) (Heteroptera: Pentatomidae) (Leal et al, 1998), Trigonotylus caelestialium (Kirkaldy) (Heteroptera: Milidae) (Kakizaki and Sugie, 2001), and Stenotus rubrovittatus (Heteroptera: Milidae) (Yasuda et al, 2008) have been identified. Synthetic pheromones have been used for monitoring P. stali (Nakamura and Nishino, 1999), R. pedestris , and T. caelestialium (Ishimoto et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In Japan, the aggregation pheromones of Plautia crossota stali Scott (Heteroptera: Pentatomidae) (Sugie et al, 1996), Riptortus pedestris (Fabricius) (Heteroptera: Alydidae) (ϭR. clavatus) (Leal et al, 1995) and Eysarcoris lewisi (Distant) (Heteroptera: Pentatomidae) (Takita et al, 2008), and the sex pheromones of Piezodorus hybneri (Gmelin) (Heteroptera: Pentatomidae) (Leal et al, 1998), Trigonotylus caelestialium (Kirkaldy) (Heteroptera: Milidae) (Kakizaki and Sugie, 2001), and Stenotus rubrovittatus (Heteroptera: Milidae) (Yasuda et al, 2008) have been identified. Synthetic pheromones have been used for monitoring P. stali (Nakamura and Nishino, 1999), R. pedestris , and T. caelestialium (Ishimoto et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Trigonotylus caelestialium and S. rubrovittatus females release sex attractants to attract males [25]- [28]. However, it remains unclear how attractants influence the behavior of bugs in narrow cages; thus, the males and females are separated in the selection test to avoid any interaction between sexes.…”
Section: Discussionmentioning
confidence: 99%
“…The sex pheromone of S. rubrovittatus females consists of three principal components; hexyl butyrate, (E)-hex-2-en-1-yl butyrate, and (E)-4-oxohex-2-enal (Yasuda et al, 2008). To collect the compounds released by individual females, they were separately introduced into side-armed glass tubes sealed with black screw caps fitted with Teflon®-faced rubber liners (see Oku & Yasuda, 2010).…”
Section: Collection Extraction and Quantitative Analysis Of Airbornementioning
confidence: 99%